Splice receptor-site mutation c.697-2A>G of the COL1A1 gene in a Chinese family with osteogenesis imperfecta - Zhai, Naixiang (Intractable Rare Dis Res, 2019)
Osteogenesis imperfecta (OI) is a genetic disorder characterized by bone fragility and blue sclerae, which are mainly caused by a mutation of the COL1A1 or COL1A2 genes that encode type I procollagen. Mutations in the splice site of type I collagen genes are one of the mutations that cause OI and usually lead to a mild or moderate OI phenotype. A heterozygous A to G point mutation in intron 9 at the -2 position of the splice receptor site of COL1A1 was identified in a family with type I or IV OI. Three affected individuals in four generations of one family all presented with several clinical symptoms. They all had pectus carinatum, flat feet, gray-blue sclerae, and normal stature, teeth, hearing, and vision. Forearm fractures, small joint dislocations, and muscle weakness were all present in the patient's father and grandmother, who presented with a moderate type IV phenotype. The 10-year-old proband with type I OI had suffered a fracture twice, but had no history of joint dislocation or skin hyperextensibility. Charting the family helped to identify clinical symptoms in patients with mutations at the N-terminal of type I collagen genes.